Implementasi Manajemen Madrasah Adiwiyata di MAN 1 Samarinda - Julaiha, Siti; Maula, Ishmatul (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
This article is a qualitative research that aims to describe the implementation of environmentally sound school management in MAN 1 Samarinda. This school began to focus on becoming a school adiwiyata in 2015 and managed to achieve the achievement as a provincial school adiwiyata in 2017. Implementation of this adiwiyata program as a manifestation of the vision of MAN 1 Samarinda, which is MAN 1 Samarinda as a religious-based school is to realize the human resources has aqidah islam and morality, smart, independent, competitive, able to build partnership and concern for environmental sustainability. The Adiwiyata school program at MAN 1 Samarinda was designed by the Adiwiyata MAN 1 Samarinda program team which includes 4 components, ie environmentally sound policies, environmental-based curriculum implementation, participatory based activities and environmentally friendly use of facilities. Supporting factors in the implementation of the adiwiyata program in MAN 1 Samrinda, which is good cooperation of all components of the school community, environmentally friendly facilities and infrastructure and support from outside parties, one of them Environment Agency (DLH). While the inhibiting factor in the implementation of the adiwiyata program is the cost or budget and students’ awarenees of the environment. Keywords: Adiwiyata School Management